Transforming growth factor-β1 impairs lymph node homing of dendritic cells by downregulating C-type lectin receptor-2 expression. (October 2018) - Gujar, Ravindra; Sen, Pradip
Highlights: TGF-β1 impedes DC migration to regional lymph nodes by reducing CLEC-2 expression. TGF-β1 downregulates CLEC-2 expression in DCs via c-Src. c-Src silencing improves lymph node homing of TGF-β1-treated DCs restoring CLEC-2 level. Abstract: Trafficking of dendritic cells (DCs) from peripheral tissues to draining lymph nodes is a prerequisite for induction of adaptive immunity. An immunosuppressive cytokine transforming growth factor (TGF)-β1, however, inhibits migration of DCs by downregulating the expression of chemokine receptor CCR-7. Whether TGF-β1 engages any other receptor to mediate this inhibitory effect is currently unknown. In this article, we report that TGF-β1 attenuated the lymph node homing ability of mouse DCs by reducing C-type lectin receptor-2 (CLEC-2) expression. Notably, TGF-β1 inhibited CLEC-2 expression in DCs via c-Src. DCs silenced for c-Src were resistant to TGF-β1-induced inhibition of CLEC-2 expression. Furthermore, silencing of c-Src substantially improved the lymph node homing capacity of TGF-β1-treated DCs by restoring CLEC-2 expression. These results document a critical role for c-Src and CLEC-2 in TGF-β1-mediated impairment of DC migration and define a previously unknown mechanism by which TGF-β1 attenuates the lymph node homing ability of DCs.